PENGGUNAAN GAME EDUKATIF WORDWALL DALAM PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MINAT DAN KETERAMPILAN LITERASI SISWA KELAS V SD - Winarni; Bambang Putut Setiyadi, Dwi; Mulyatno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low active participation and less than optimal literacy skills of fifth-grade students in learning. The study aims to describe the implementation and assess the impact of Wordwall educational games in interactive learning on students' learning interest and reading literacy skills. A Classroom Action Research (CAR) method with two cycles was employed, involving 11 fifth-grade students at SD Negeri 5 Pracimantoro. Data collection techniques included observation, interviews, questionnaires, literacy tests, and documentation. The results showed a significant increase in student learning interest, from the pre-cycle category dominated by "moderate" interest to the "high" and "very high" categories in Cycle II. Reading literacy skills also improved, with the majority of students reaching the "good" and "very good" categories by the end of Cycle II. The study concludes that the implementation of Wordwall educational games in interactive learning is effective in creating a more engaging, enjoyable, and meaningful learning atmosphere, thereby enhancing both student interest and literacy skills. Keywords: Wordwall, interactive learning, learning interest, literacy, classroom action research